The Early Medieval Settlement Remains from Flixborough, Lincolnshire The Occupation Sequence, c. AD 600-1000 - Atkinson, David (Historic England, 2007)
Volume 1 focuses on the occupation sequence, looking at the structural and stratigraphical evidence from the site, and interpreting the changing use of the site during its lengthy occupation. This interpretation of the occupation sequence forms the basis for all thematic discussions in Volumes 3 and 4. It also examines the evidence for burials at the site, and places this into the wider context of sepulchral practices in mid and late Saxon England. Finally there is discussion of the osteological remains themselves, giving hints of the demographic spectrum of the inhabitants, their lifestyles and ailments.